PENGARUH LOKASI, STORE ATMOSPHERE DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN PELANGGAN PADA COFFEE SHOP EXTRACT COFFEE PEKANBARU - Pratama Anugrah Aditiya; Wijayanto Gatot; Taufiqurrahman Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Due to the development of a growing business, it forces all business people to continue tomaintain and increase the value of their business. This situation is no exception to the coffee shopbusiness, which as it is known that the development of coffee shops continues to occur not only inIndonesia but also in Pekanbaru. This study aims to determine the effect of location selection,store atmosphere and brand image on purchasing decisions and customer satisfaction at theCoffee Shop Extract Coffee Pekanbaru. This study uses a quantitative approach. The sample inthis study were 100 consumers domiciled in Pekanbaru who had come to Extract Coffee. Thesampling technique used in this study is non-probability sampling with purposive samplingmethod, namely sampling based on certain criteria. The results of this study indicate that bothlocation, store atmosphere and brand image have a positive and significant effect on purchasingdecisions. Likewise, purchasing decisions have a positive and significant effect on customersatisfaction. Furthermore, it is known that location, store atmosphere and brand image have apositive and significant effect on customer satisfaction through the purchase decision of ExtractCoffee Pekanbaru. Keywords: location, store atmosphere, brand image, purchasing decisions, customersatisfaction